Novel insights on energy transfer processes in [Ce4+/Ce3+]-Er3+-doped tellurite glass. Issue 4 (15th February 2023) - Pinto, I.C.; Falci, R.F.; Rivera, V.A.G.; Guérineau, T.; LaRochelle, S.; Messaddeq, Y.
Abstract: Previous works have been already reported on multiphonon-assisted non-resonant energy transfer in Ce 3+ -Er 3+ -doped tellurite glasses. However, it is not clear the mechanism of the radiative emission of Er 3+ centered at 1530 nm. In this paper, we reported a better understanding of the mechanism of interactions between those two rare-earth ions via a systematic study. For that, we will explore the energy transitions between Ce 4+ /Ce 3+ and Er 3+ ions in a tungsten-tellurite glass to both emission (in the near infrared) and upconversion (in the visible) spectrum. Here, Ce 4+ and Ce 3+ were obtained in an Er 3+ -doped tellurite glasses via the addition of different concentrations of CeO2 as part of the composition of the samples. Emission spectrum, under a 980 nm excitation, giving rise to a series of interactions between Ce 3+ ↔Er 3+ resulting in: (i) a subtle increase of the Er 3+ emission intensity in the near-infrared region for 0.1 mol% of CeO2, and then a decrease in the emission for higher CeO2 concentration in both cases without any significant increase in the bandwidth, and (ii) a decrease of the visible upconversion emission intensity with the addition of CeO2 . Such interactions are achieved via a coupling yielding and energy transfer from both rare-earth ions.